Conhecimento e práticas de cirurgiões-dentistas acerca do processo de fotopolimerização e avaliação do tempo de ativação na adesão de bráquetes ortodônticos - Sena, Nara Juliana Custódio de (2024)
The aim of this work was (1) to investigate the polymerization techniques used by private dental practitioners and their general knowledge regarding the light-curing process, and (2) to evaluate the degree of conversion (DC) and the shear bond strength (SBS) of an orthodontic resin used to bond brackets to the enamel surface under varying irradiance and curing times using different commercial light-curing units (LCUs). In the first chapter of this study, a questionnaire attached to an invitation text to participate in the survey was sent electronically by email and social media to dentists working in private practice. This questionnaire consisted of 26 mandatory questions and was divided into 3 sessions (professional profile, knowledge about the light-curing devices, and knowledge about the polymerization technique). A total of 487 professionals answered the questionnaire, and data analysis was performed using descriptive statistics and frequency analysis (p<0,05). Gaps in specific knowledge among the professionals about the light-curing process as well as variations in the techniques used for this purpose were observed. In the second chapter, to assess the SBS of the bracket-enamel interface, light-curing was performed with BluephaseÒN or EliparTM Deep Cure-L for 5 or 20 s or with ValoTM Cordless for 3, 5, or 20 s (n=30). The SBS of the bracket-enamel interface and the DC (n=21) of the Transbond XT® composite resin used to bond the bracket to the tooth surface were evaluated. Data were submitted to the Shapiro-Wilk normality test, expressed as mean and standard deviation values, and compared using ANOVA/Bonferroni or Student's ttests. The curing time significantly affected the SBS means (p < 0.05). At 5 s of curing time, there were no statistical differences among the LCUs. However, an increase in SBS was observed when ValoTM Cordless was used for 20 s. The curing time did not affect SBS for BluephaseÒ N and EliparTM deep cure groups; nonetheless, for the specimens cured with Valo TM Cordless, SBS increased approximately 35% - 36% when the exposure time of 20 s was used. There was no difference in DC among the LCUs at 20 s, whereas at 5 s BluephaseÒN presented higher values than EliparTM Deep Cure-L and ValoTM Cordless, which were statistically similar. When evaluated separately, ValoTM Cordless and BluephaseÒN did not present differences in DC at 5 and 20 s, whereas for EliparTM Deep Cure-L, the increase in curing time to 20 s resulted in higher DC. The use of ValoTM Cordless for 3-second light-curing resulted in a decrease of DC compared to 5 and 20 s. It can be concluded that different irradiance and exposure times affect the SBS and DC of orthodontic composite resins.